PERBEDAAN SKOR PLAK GIGI, pH SALIVA, DAN STATUS ORAL HYGIENE PADA PEMAKAI DAN BUKAN PEMAKAI ALAT ORTODONTI CEKAT - Wahid Marlisa; Henry Setyawan Susanto; Lintang Dian Saraswati; M. Sakundarno Adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Orthodontic appliances can have the effect of changing the environment of oral cavity and composition of oral flora, changes in the amount of plaque, pH of salivary and oral hygiene which can cause dental and oral diseases such as dental caries and periodontal disease. The aim of this studyis to know the difference of dental plaquescore, salivary pH,and oral hygiene status between users and non users of fixed orthodonticappliance. This type of research is an observational analytic with cross sectional design. Subjects in this study amounted to 100 respondents consisting of two groups of users and non users of fixed appliance orthodontic. The technique sampling is proportional stratified random sampling. Identification of dental plaquewere measured by disclosing solution, salivary pH were measuredby Universal CG and oral hygiene status were measured by summing debris score and calculus score from each subject. The result showed that the difference of plaque scores between the users and non users of fixed appliance orthodontic with p = 0,769, the difference of saliva pH between users and non users of fixed appliance orthodontic with p = 0,264, and the difference of oral hygiene status between users and non users of fixed appliance orthodontic with p = 0.397. Conclusion: there was no significant difference of dental plaquescore, salivary pH,and oral hygiene status between users and non users of fixed orthodonticapplianceof students of Economics and Business Diponegoro University.